2004
DOI: 10.1890/03-3050
|View full text |Cite
|
Sign up to set email alerts
|

Functional Redundancy Supports Biodiversity and Ecosystem Function in a Closed and Constant Environment

Abstract: The role functionally redundant species play in ecosystem function has not been adequately investigated. To study this, we examined species richness and an ecosystem function, cellulose decomposition, while environmental conditions were held constant. Our hypotheses were (1) increasing species richness will have no effect on rates of cellulose decomposition and (2) species richness will decline over time in functionally redundant communities. A relatively simple microcosm-based system to manipulate complex mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
158
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 224 publications
(163 citation statements)
references
References 22 publications
4
158
1
Order By: Relevance
“…As the main assumption made by the neutral model is the functional equivalence of taxa (Hubbell, 2001), no compositional changes, but rapid functional adaptations of dispersed populations, should occur when they arrive in a new habitat, as functional plasticity is expected to be high. This corresponds to the adjustment scenario of Comte and del Giorgio (2011) and is supported by studies that have shown that microbial communities can functionally adapt to different environments even without drastic changes in composition, and that microbial communities of different composition can perform equally owing to their functional redundancy (Wohl et al, 2004;Wertz et al, 2007;Comte and del Giorgio, 2010;Werner et al, 2011).…”
Section: Introductionmentioning
confidence: 52%
“…As the main assumption made by the neutral model is the functional equivalence of taxa (Hubbell, 2001), no compositional changes, but rapid functional adaptations of dispersed populations, should occur when they arrive in a new habitat, as functional plasticity is expected to be high. This corresponds to the adjustment scenario of Comte and del Giorgio (2011) and is supported by studies that have shown that microbial communities can functionally adapt to different environments even without drastic changes in composition, and that microbial communities of different composition can perform equally owing to their functional redundancy (Wohl et al, 2004;Wertz et al, 2007;Comte and del Giorgio, 2010;Werner et al, 2011).…”
Section: Introductionmentioning
confidence: 52%
“…Microbial BEF studies use DNA-based molecular diversity assessment techniques bearing no diagnostic means to determine which of the species is contributing to the observed function (Bell et al, 2009). Positive BEF relationships are most often observed with narrow functions (e.g., methane oxidation (Levine et al, 2011), polymer degradation (Wohl et al, 2004;Peter et al, 2011) or pesticide degradation (Monard et al, 2011)), where species are brought together to determine which all contribute to the specific function in the respective experimental setup. Hence, BEF studies in microbial ecosystems where species that are actively contributing to ecosystem functioning cannot be pinpointed will give biased results, often concluding functional redundancy to be occurring which actually is either a lack of niche heterogeneity or cumulative counting of 'seed bank' species that are not actively contributing to the measured function.…”
Section: Synthesismentioning
confidence: 99%
“…A number of gaps in the knowledge of environmental microbial communities are fundamental to the absence of microbes on the global biodiversity conservation agenda (Bodelier, 2011), the inability to link microbial species to the processes they catalyze as well as the assumed high functional redundancy in microbial communities being the most crucial ones (Bodelier, 2011). These issues may be the reason why links between microbial diversity and ecosystem processes have been observed only for processes carried out by narrow groups of microbes carrying out a specific process (e.g., chitin and cellulose degradation) (Wohl et al, 2004;Peter et al, 2011) in diversity manipulation or artificial community experiments. The often-observed saturating species-function curves in these experiments, interpreted as functional redundancy, may be caused by including species not actively contributing to function.…”
Section: Introductionmentioning
confidence: 99%
“…Because 16S rRNA is considered a proxy for bacterial activity, these bacteria are significantly enriched in the biofilm community, and these data are consistent with described ecological role of these bacteria as putative denitrifiers, we find this explanation unlikely. Alternatively, we propose that the replacement of Proteobacteria with Firmicutes in the ANL reactor over time without a corresponding change in operation indicates these bacteria are functionally redundant and thus a change in composition does not affect reactor performance (Fernandez et al, 2000;Wohl et al, 2004).…”
Section: Lack Of Relationship Between Dominant Members and Reactor Pementioning
confidence: 99%